SPE601 : Performance analysis / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course introduces the concepts of performance analysis in coaching process. Aspects of discussion will include manual notational analysis and video analysis in collecting data, objectivity and reliability, analysis, interpretation and presentation of data towards clients.